Pengaruh Pemahaman Tri-Nga Dan Motivasi Diri Terhadap Minat Berkarir Mahasiswa Akuntansi Di Bidang Perpajakan - Jaemah, Siti; Utami, Citra Kharisam; Nurfauziah, Farah Latifah (POLITEKNIK LP3I, 2024)
This research is categorized as quantitative descriptive method research, where the research instruments are observation, interviews and questionnaires. The sampling technique in this study used the hair formula. The population in this study were accounting students in the city of Bandung. The sample taken was 115 respondents, with the analysis used in this study including the research instrument test, classical assumption test, multiple linear test, t test, f test and determination test.The results of this study are the tri-ga understanding variable (X1) has a positive and significant effect on the career interest of accounting students in the field of taxation (Y). Self-motivation variable (X2) has a positive and significant effect on the career interest of accounting students in the field of taxation (Y). And the tri-ga understanding variable (X1), self-motivation (X2) simultaneously affects the career interest of accounting students in the field of taxation (Y).